ChemInform Abstract: A Rapid Route for the Preparation of Pyrimido[5, 4‐d]‐ and Pyrido[3, 2‐d]oxazoles. Issue 34 (August 2015) - Lemaire, Lucas; Leleu‐Chavain, Natascha; Tourteau, Aurelien; Abdul‐Sada, Alaa; Spencer, John; Millet, Regis
Abstract The substrate (I) is found to be a very efficient building block for the construction of the title heterocycles.